Geostrategic importance of Antarctica in the geopolitics of the South Atlantic - Fernández Alonso, Daniel Alejandro; Castillo Bocalandro, Diana Rosa; Camacho Solís, Helen (Instituto Superior de Relaciones Internacionales "Raúl Roa García", 2021)
In the XXI century, the South Atlantic is an area of great relevance in the geopolitical context where it is framed. The interests on it exceed the geographical limits imposed by the riparian countries between the Equator Line and the Antarctic continent. Multiple interests converge on this part of the globe, both from the States parties to the "South Atlantic Peace and Cooperation Zone" and from foreign powers. Identifying the factors that make Antarctica of geostrategic importance in the geopolitical design of the extended South Atlantic is a matter of great interest in the current context and therefore it is the proposed research objective. Its natural resources, its strategic geographical position, as well as the claims on it, make the Antarctic region one of the points of view for the great centers of power. En pleno siglo XXI el Atlántico Sur es una zona de gran relevancia en el contexto geopolítico donde se enmarca. Los intereses sobre el mismo rebasan los límites geográfi cos que imponen los países ribereños entre la Línea del Ecuador y el continente antártico. Sobre esta parte del globo confl uyen múltiples intereses, tanto de los Estados partes de la “Zona de Paz y Cooperación del Atlántico Sur” como de potencias extranjeras. Identifi car los factores que hacen de la Antártida, de importancia geoestratégica en el diseño geopolítico del Atlántico Sur extendido constituye un asunto de sumo interés en el contexto actual y por tanto el objetivo de investigación propuesto. Sus recursos naturales, su estratégica posición geográfi ca, así como los reclamos sobre ella, convierten a la región antártica en uno de los puntos de mira para los grandes centros de poder.